Pengaruh Gaya Kepemimpinan dan Stres Kerja terhadap Turnover Intention di Mediasi Kepuasan Gen Z PT Win Era Digital - Priska Vibri Safira; Muhammad Syihabuddin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This investigation is designed to investigate the impact of leadership style and work stress on attrition intention, with job satisfaction serving as a mediating variable, among Generation Z employees of PT Win Era Digital. A saturated sampling technique was employed to select a sample of all Gen Z employees, resulting in a total of approximately 80 individuals. The study employed a quantitative explanatory approach. The direct and indirect effects were both tested using the Sobel test, and data were collected using a Likert scale questionnaire and analyzed using simple regression data analysis techniques. In Generation Z employees at PT Win Era Digital, the results indicated that turnover intention was significantly and negatively influenced by leadership style, while turnover intention was significantly and positively influenced by job stress. A leadership style that is effective can reduce the likelihood of employees leaving the organization, whereas increased job stress actually promotes an increase in turnover intention. Furthermore, leadership style has a beneficial impact on job satisfaction, whereas work stress has a detrimental impact on it. Research has also demonstrated that job satisfaction has a detrimental impact on turnover intention and partially mediates the impact of leadership style and job stress on turnover intention.